Does meconium contaminated amniotic fluid affect intestinal wall thickness and functional outcome in patients with anterior abdominal wall defects? - Melanie Kapapa; Teresa Rieg; Alexandre Serra (Wolters Kluwer Medknow Publications, 2022)
Background: Gastroschisis (GS) and omphalocele (OC) are congenital abdominal wall defects, the main difference between is the direct exposure of intestinal loops in amniotic fluid in children with a GS. This leads to a reduced primary closure rate and a higher number of intraoperative abnormalities and post-operative complications. Aims and Objectives: We analysed abdominal wall defect patients over an 11-year period, aiming to assess the influence of meconium-contaminated amniotic fluid. This study has different objectives to show the consequence of functional outcome of abdominal wall defects (AWD) children in reliance to colour of amniotic fluid, to assess the effect of reduced bowel exposure time to meconium contaminated amniotic fluid on edematous inflammatory thickening of the bowel loops, to show an positively influence in the number of primary AWD closures, to demonstrate a reduced incidence of post-natal complications and to verify a better outcome of OC children because of failing exposure to amniotic fluid. Methods: A retrospective, observational case-control design was used to compare GS (n = 36) and OC (n = 18) children. Physical data, colour of amniotic fluid, pre- and perinatal problems, operative complications and surgical technique, post-operative complications, duration of intensive care unit (ICU) stay, mechanical ventilation, parenteral nutrition, commencement of oral feeding and total hospital stay were collected. Data were analysed with descriptive methods, t-test and non-parametric tests such as Wilcoxon and Kruskal-Wallis were performed in addition to the analysis of variance, including post hoc testing accepting a confidence interval of 95% (P < 0.05) by using IBM SPSS software, version 23 (IBM, Illinois, USA). Results: Rate of meconium-contaminated amniotic fluid is significantly higher in GS compared to OC (P < 0.001), delivery problems such as congenital infections are also significantly higher (P < 0.001), this yields in significantly more bowel loops anomalies and problems during surgery (P < 0.036) but had no significant influence on primary abdominal wall closures rate (P = 0.523). The post-surgical outcome of OC was significantly better as compared to GS. Within the GS, those with swollen intestines had significantly longer ICU stays (P = 0.045) due to extended mechanical ventilation (P = 0.007), parenteral nutrition (P = 0.011) and delayed initiation of oral feeding (P < 0.001. Same results were found for the duration of ICU stay (P = 0.008), mechanical ventilation (P = 0.006), parenteral nutrition (P = 0.011) and delayed initiation of oral feeding (P < 0.001) in secondary closures as compared to primary abdominal wall closures in the GS group. Conclusions: Worsen functional short-term outcome of GS children was directly addicted to meconium contamination of amniotic fluid due to swollen intestines and because of this more post-surgical problem including significantly extended hospital stays were observed.